A new oridonin analog suppresses triple-negative breast cancer cells and tumor growth via the induction of death receptor 5. Issue 2 (1st October 2016) - Wu, Jing; Ding, Ye; Chen, Chuan-Huizhi; Zhou, Zhongmei; Ding, Chunyong; Chen, Haiying; Zhou, Jia; Chen, Ceshi
Highlights: The oridonin analog CYD-6-28 shows much better activity than oridonin. CYD-6-28 inhibits cell proliferation and induces apoptosis in triple negative breast cancer. CYD-6-28 induces apoptosis by inducing the expression of death receptor 5 (DR5). CYD-6-28 suppresses tumor growth in mice at 5 mg/kg without affecting body weight. Abstract: Triple-negative breast cancer (TNBC) remains the leading cause of death among women with breast cancer worldwide. Oridonin is a natural anti-cancer compound that is isolated from the traditional Chinese herb Rabdosia rubescens. However, the antitumor efficacies of oridonin in the treatments of TNBC and other cancers are far from ideal. In this study, we investigated a series of newly designed oridonin analogs in terms of their actions against HCC1806 and HCC1937 TNBC cell lines and identified CYD-6-28, which significantly inhibits cancer cell proliferation and induces G2/M-phase cell cycle arrest and apoptosis. CYD-6-28 induces the expression of p21 and the cleavage of caspase-3, -7, -8 and PARP and inhibits the expression levels of Cyclin D1, FLIPL and XIAP. CYD-6-28 also inhibits the activations of STAT3 and AKT and induces the activation of ERK. We demonstrated that CYD-6-28 induces apoptosis at least partially by inducing the expression of death receptor 5 (DR5). Finally, CYD-6-28 significantly suppresses HCC1806 xenograft tumor growth in nude mice at 5 mg/kg without affecting body weight. Taken together, these results indicate that CYD-6-28 has the potential to be developed as a therapeutic agent to treat TNBC.